Phylogeography of Human and Animal Coxiella burnetii Strains: Genetic Fingerprinting of Q Fever in Belgium - Tomaiuolo, Sara; Boarbi, Samira; Fancello, Tiziano; Michel, Patrick; Desqueper, Damien; Grégoire, Fabien; Callens, Jozefien; Fretin, David; Devriendt, Bert; Cox, Eric; Mori, Marcella (Frontiers in Cellular and Infection Microbiology, 2021)
Q fever is a zoonotic disease caused by the bacteria Coxiella burnetii. Domestic ruminants are the primary source for human infection, and the identification of likely contamination routes from the reservoir animals the critical point to implement control programs. This study shows that Q fever is detected in Belgium in abortion of cattle, goat and sheep at a different degree of apparent prevalence (1.93%, 9.19%, and 5.50%, respectively). In addition, and for the first time, it is detected in abortion of alpaca (Vicugna pacos), raising questions on the role of these animals as reservoirs. To determine the relationship between animal and human strains, Multiple Locus Variable-number Tandem Repeat Analysis (MLVA) (n=146), Single-Nucleotide Polymorphism (SNP) (n=92) and Whole Genome Sequencing (WGS) (n=4) methods were used to characterize samples/strains during 2009-2019. Three MLVA clusters (A, B, C) subdivided in 23 subclusters (A1-A12, B1-B8, C1-C3) and 3 SNP types (SNP1, SNP2, SNP6) were identified. The SNP2 type/MLVA cluster A was the most abundant and dispersed genotype over the entire territory, but it seemed not responsible for human cases, as it was only present in animal samples. The SNP1/MLVA B and SNP6/MLVA C clusters were mostly found in small ruminant and human samples, with the rare possibility of spillovers in cattle. SNP1/MLVA B cluster was present in all Belgian areas, while the SNP6/ MLVA C cluster appeared more concentrated in the Western provinces. A broad analysis of European MLVA profiles confirmed the host-species distribution described for Belgian samples. In silico genotyping (WGS) further identified the spacer types and the genomic groups of C. burnetii Belgian strains: cattle and goat SNP2/MLVA A isolates belonged to ST61 and genomic group III, while the goat SNP1/ MLVA B strain was classified as ST33 and genomic group II. In conclusion, Q fever is widespread in all Belgian domestic ruminants and in alpaca. We determined that the public health risk in Belgium is likely linked to specific genomic groups (SNP1/MLVA B and SNP6/ MLVA C) mostly found in small ruminant strains. Considering the concordance between Belgian and European results, these considerations could be extended to other European countries.